Melodramatic South Asia: In Quest of Local Cinemas in the Region. (September 2017) - Pathak, Dev N.
What is remarkably unique of the popular cinema in the region of South Asia? How does it lead beyond the vexed notions of the contemporary milieu, namely, hybrid local? How does it transcend the idea of nationally restricted local too? Looking through eclectic motley of popular cinema in the region, this article seeks to unravel such questions with reflexive propositions. It paves the way to comprehend cinematic identity of the region with the adjective of 'melodrama', as perceived through the local sociocultural component. It is with the sweep of melodrama, arguably, that cinema of South Asia transcends the notions attached with the category of 'local'. In this backdrop, this article moots a probing question: What is local in the regional cinemas? Does local mean merely a vexed category in contemporary context of transnational flow? Or there is more to the category of local, beyond the existing formulations? With these questions, this article seeks to participate in the available discourse showing the regional cinema underpinned by the essentially dynamic nature and scope of the local.